The Training Using a Hanging Ball Modification Tool as an Effort to Improve Basic Volleyball Passing Techniques - Fauzan Supian; Anggi Setia Lengkana; Entan Saptani (Universitas Negeri Semarang, 2026)
This research is motivated by the low technical ability of elementary school students in volleyball underhand passing during extracurricular activities, caused by a lack of structured, repetitive, and innovative training. This study aims to analyze the effect of training using a modified hanging ball in the drill method on improving underhand passing ability. The method used was a quantitative one-group pretest-posttest preexperimental design. The subjects were 28 extracurricular students at Babakan Rancakalong Elementary School, selected using a purposive sampling technique. The research instrument was an underhand passing skills test covering initial stance, execution, and final stance. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, the paired sample t-test, and the effect size test (Cohen's d). The results showed a significant increase in underhand passing ability, indicated by an increase in the average score from 19.17 (pretest) to 26.46 (posttest), with the minimum score increasing from 12 to 18 and the maximum score from 32 to 36. Normality testing indicated a normally distributed data (p > 0.05). A paired sample t-test obtained a significance value of 0.000 (p < 0.05), indicating a significant difference between before and after the treatment. The effect size of 3.64 indicated a very large effect. The conclusion of this study is that training using a modified hanging ball in the drill method effectively improves elementary school students' basic underhand passing skills and can be used as an alternative, innovative, systematic, and applicable learning method.